Pengaruh Diversity, Turnover Intention dan Kepuasan Kerja Terhadap Pengembangan Potensi Aparatur Desa Bintan Buyu Kabupaten Bintan - Nurhasanah Nurhasanah; Risdy Absari Indah Pratiwi (Bahtera Inovasi, 2020)
This study aims to explain the effect of Diversity, Turnover Intention and Job Satisfaction on the Development of Potential Apparatus of Bintan Buyu Village, Bintan Regency. The study population was the Village apparatus in Bintan Regency, Riau Islands Province. The number of samples were 73 Village Apparatuses in Bintan Buyu Subdistrict, Bintan Regency consisting of 6 Villages, namely Tembeling Tanjung Village, Tembeling Village, Bintan Buyu Village, Penaga Village, Pengujan Village and Pangkil Village. For the efficiency and effectiveness of the research, the Village Apparatus in Pangkil Village is not included in the data because of access to Pangkil Village by sea. This type of research is quantitative research. The validity and reliability tests were performed on the questionnaire. Data were tested through the Classical Assumption Test, namely the Data Normality Test, the Data Multicollinearity Test and the Data Heteroscedasticity Test. Data were analyzed using multiple linear regression analysis, including t test, F test and the coefficient of determination. The results showed that the Diversity (X1) and Job Satisfaction (X3) variables partially had a significant effect on Potential Development, while the Turnover Intention variable (X2) partially had no significant effect on the Potential Development variable (Y). F test results obtained calculated F value of 53,548 with F value of table 2.74 to identify that the variable Diversity, Turnover Intention and Job Satisfaction simultaneously influence the Potential Development variable (Y). Based on the coefficient of determination test, about 70% of the Potential Development variable is influenced by the Diversity, Turnover Intention and Job Satisfaction variables. And 30% is influenced by other factors not explained in this study.